Pengaruh Penggunaan Media Google Site terhadap Keaktifan Belajar Siswa Kelas IV SD Negeri 101866 Batang Kuis - Nasution, Maysarah; Sitepu, Melyani Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Current developments have triggered an increase in the teaching and learning process which has begun to change using technological media during procedures. Thus, the aim of this research is to find out how the use of Google Sites media affects the active learning of class IV students at SD Negeri 101866 Batang Kuis. By using population and sample data from SD Negeri 101866 Batang Kuis, this research uses a quantitative approach. The data obtained is based on the results of distributing questionnaires and observing the implementation of Google Sites learning using SPSS 25 software and based on the results of a significance level of 0.05 with a variable significance value of 0.043. This shows the large influence of Google Site Media on learning activities while the residual value is 0.065 > 0.05, so the resulting normality test findings are significant. It is considered homogeneous because the significance value of the homogeneity test is 0.784 > 0.05. Thus, it can be said that fourth grade students at SD Negeri 101866 benefit from using Google Site Media in their active learning.